PARTICLE DISPERSION MODEL FOR RADIOACTIVE RELEASE DOSE CALCULATION (CASE OF MURIA PENINSULA-CENTRAL JAVA) - (NIM: 20206003), SUNARKO
Assessment for radioactive pollutant dispersion was performed for postulated accident condition using source-term taken from Three-Mile Island unit 2 PWR accident. Modelling was performed using Lagrangian Particle Dispersion Method (LPDM) to provide numerical solution to advection-diffusion equation. Movement of radioactive particle by wind-field and turbulen diffusion was modelled using random-walk / Monte-Carlo techniques using non-Gaussian diffusion coefficient and Pasquill A-F stability to accommodate spatially non-uniform wind speed, turbulent diffusion coefficient and topography.